Speech Acts in the Social Context of the Film "Honeymoonish" by Elie El Semaan: A Pragmatic Review According to John Austin - Noviana Yusanti; R. Edi Komarudin; Rohanda Rohanda (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This study aims to analyze speech acts in the social context of the film Honeymoonish by Elie El Semaan using the theoretical framework of pragmatics according to John Austin. Speech acts are categorized into three types: locution, illocution, and perlocution. Through a qualitative approach, this research identifies how dialogues in the film reflect social interactions among characters and the meanings contained within them. Data is obtained through the analysis of key scenes that highlight verbal and non-verbal communication. The results of the study show that speech acts in this film not only function as communication tools but also as a medium to express emotions, conflicts, and relevant social values. Additionally, the study highlights the role of context in shaping the interpretation of speech acts, as well as the ways in which power dynamics and social hierarchies influence character interactions. By examining the intricacies of language use in Honeymoonish, this research underscores the importance of pragmatics in understanding the subtleties of human communication. These findings are expected to contribute to the study of pragmatics and film analysis, as well as enrich the understanding of social dynamics in the context of contemporary cinema.